Ratib Samman as a Local Islamic Ritual: Religious Meaning, Moral Discipline, and Social Solidarity in Minangkabau Society - Prima Dini Susanti; Silfia Hanani; Muhammad Taufik (BELIEF: Sociology of Religion Journal, 2025)
This study examines Ratib Samman as a local Islamic ritual practiced in Jorong Salimpariak, West Sumatra, and analyzes its significance from the perspective of the sociology of religion. Using a qualitative approach that combines participant observation, in-depth interviews, and textual analysis of ritual recitations (radai), this research explores how Ratib Samman functions as a form of lived Islam embedded in local social life. The findings show that Ratib Samman is not merely a devotional practice but a multifaceted ritual that reinforces social solidarity, transmits moral and religious values, and shapes embodied religious dispositions. The use of religious poetry and synchronized bodily movements enables participants to internalize theological teachings while fostering collective identity and moral discipline. Furthermore, the ritual plays an important role in providing meaning and emotional support for individuals and families, illustrating how religious practices respond to social and existential concerns. This study contributes to the sociology of religion by demonstrating that local Islamic rituals should be understood as active social processes rather than passive outcomes of cultural acculturation. By foregrounding ritual practice, embodiment, and symbolic meaning, the study offers insight into how religion continues to shape moral life and social cohesion in contemporary Muslim communities.